1996
DOI: 10.1074/jbc.271.31.18350
|View full text |Cite
|
Sign up to set email alerts
|

Formation of STAT5-containing DNA Binding Complexes in Response to Colony-stimulating Factor-1 and Platelet-derived Growth Factor

Abstract: Colony-stimulating factor (CSF-1) activates several members belonging to the STAT (signal transducers and activators of transcription) family of transcription factors. We investigated the DNA binding complexes activated by CSF-1 in several cell lines and compared them with complexes activated by platelet-derived growth factor and interleukin 3. Our results indicate that the SIF-A complex activated by CSF-1 and platelet-derived growth factor may contain STAT3/STAT5 heterodimers binding to the high affinity SIF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 37 publications
4
39
0
1
Order By: Relevance
“…In these reports, JAK 1, JAK 2, STAT 1, STAT 3 and /or STAT 5 were tyrosine-phosphorylated following receptor activation in response to EGF, PDGF, CSF-1 or SCF stimulation. [65][66][67][68][69][70] These studies, in conjunction with the findings reported here, imply a possible role for the JAK-STAT pathway in FLT3 receptor signaling. Whether this is a result of phosphorylation of JAKs by the activated receptor via a direct interaction of the two proteins or is indirect and results from phosphorylation and activation of other tyrosine kinases (eg SRC family members) or intermediate adaptor proteins is not known and will require further study.…”
Section: Discussionsupporting
confidence: 76%
“…In these reports, JAK 1, JAK 2, STAT 1, STAT 3 and /or STAT 5 were tyrosine-phosphorylated following receptor activation in response to EGF, PDGF, CSF-1 or SCF stimulation. [65][66][67][68][69][70] These studies, in conjunction with the findings reported here, imply a possible role for the JAK-STAT pathway in FLT3 receptor signaling. Whether this is a result of phosphorylation of JAKs by the activated receptor via a direct interaction of the two proteins or is indirect and results from phosphorylation and activation of other tyrosine kinases (eg SRC family members) or intermediate adaptor proteins is not known and will require further study.…”
Section: Discussionsupporting
confidence: 76%
“…Stat5 was ®rst characterized in mammary gland tissue as a prolactin-inducible transcription factor (Wakao et al, 1994), but has been shown to be activated by numerous cytokines and growth factors in diverse cell types (Azam et al, 1995;Friedmann et al, 1996;Mui et al, 1995;Ru -Jamison et al, 1995;Gouilleux et al, 1995;Novak et al, 1996;. Two highly related Stat5 proteins, denoted Stat5a and Stat5b have been described, which are able to form homo-or heterodimers after phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Stat1, 3 and 5 have also been shown to be activated by PDGF (Novak et al, 1996;Patel et al, 1996;Sadowski et al, 1993;Silvennoinen et al, 1993). Therefore, we investigated the consequences of deleting Stat6 on the activation of these other STAT family members.…”
Section: E Ect Of Stat6 Deletion On Pdgf Induction Of Stat Dna Bindinmentioning
confidence: 99%
“…Among the PDGF isoforms, PDGF BB is the human homolog of the v-sis oncogene product Doolittle et al, 1983;Water®eld et al, 1983). Jak1, Jak2 and Tyk2 (Vignais et al, 1996), as well as Stat1, Stat3 (Sadowski et al, 1993;Silvennoinen et al, 1993), Stat5 (Novak et al, 1996;Patel et al, 1996) and Stat6 (Patel et al, 1996) have been implicated among the many PDGFR downstream e ector molecules (Claesson-Welsh, 1996).…”
Section: Introductionmentioning
confidence: 99%